Seasonal incidence and efficacy of nano-thiamethoxam on tomato leaf miner, Liriomyza trifolii (Burgess) (Diptera: Agromyzidae) - Saad, Mohammed A. A.; Ahmed, Ahmed M. M.; Abdu-Allah, Gamal A. M.; Ezz El-Din, Hossam A.; Mahmoud, Hend A.; Othman, Ali A. (Journal of Phytopathology and Disease Management, 2019)
Seasonal incidence of tomato leaf miner, Liriomyza trifolii (Burgess) (Diptera: Agromyzidae), and evaluation of the new nano-formulation of thiamethoxam insecticide under climatic factors that supplying the vital knowledge for successful integrated pest management (IPM) programs. This study was conducted in two successive seasons 2017-18/ 2018-19 on variety (no. 765) of tomato that cultivated at the plant protection experimental Farm, Faculty of Agriculture, Assiut University, Assiut, Egypt. The numbers of mines on the tomato leaf were recorded from the first of November to the first of the February in the two seasons. The highest peak of mines was 28.34 mines/ plant in the 13th of December, 2018, while, it was 41.8/ plant in the January1st, 2019. Further, the climatic factor analysis during the two studied seasons demonstrated that the relative humidity was the most efficient factor (52.49 % out of 91.46 %), while the temperature was the least effective one (8.67% out of 91.46%). The nano thiamethoxam at the recommended dose (1x) of neonicotinoid insecticide significantly reduced the mines compared to traditional thiamethoxam. Furthermore, the half recommended dose of nano thiamethoxam in the two tested seasons was equal in the efficacy to the traditional thiamethoxam (1x). The reduction percentages were 86.87, 75.81 and 68.67 for nano-thiamethoxam (1x), thiamethoxam (1x), and nano- thiamethoxam (Â½ x), respectively, in 2017-18 for the first spray. In the same corresponding treatments, the values recorded were 78.94, 65.61and 62.75% in the second spray. Results of the second season (2018-19) were in the same line, where, the reduction percentages were 84.23, 76.43 and 62.43% at first spray, while the second spray were 72.95, 65.40 and 59.31% for nano-thiamethoxam (1x), thiamethoxam (1x) and nano- thiamethoxam (Â½ x), respectively. These results suggested that, the relative humidity was the main climatic factor effect on the mines population of Lirimyza trifolii. The nano-thiamethoxam was significantly reduced the pest population. Results of this study highly recommend using nano formulation in applying of IPM leaf miner programs.